2021
DOI: 10.1002/srin.202100526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulfur Content on Evolution of Nonmetallic Inclusions in Low Sulfur Al‐Killed Steels during Heat Treatment

Abstract: Herein, the effect of total sulfur (T.S) on the transformation of inclusions in Al‐killed steels is investigated through lab experiments and kinetic calculations. During the heating process, CaS content in inclusions obviously rises up, while the CaO content reduces. The CaO content in inclusions with 11 ppm S in steel is higher than 15%, while it is less 5% for the steel with 25 ppm S. The initial CaO–Al2O3 inclusions before heating change to CaS–MgO–Al2O3 at 1200 °C. The higher T.S promotes the transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…To improve the performance of steel products, calcium treatment is commonly applied to modify the amount of Al 2 O 3 inclusion and prevent nozzle clogging during the production of Al-killed steels. [1][2][3][4] Cored wire injection technology has attracted considerable attention owing to its better removal of inclusions, simple operation, and low cost. [5,6] However, its calcium yield is unstable, which restricts the high-quality development of steelmaking.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the performance of steel products, calcium treatment is commonly applied to modify the amount of Al 2 O 3 inclusion and prevent nozzle clogging during the production of Al-killed steels. [1][2][3][4] Cored wire injection technology has attracted considerable attention owing to its better removal of inclusions, simple operation, and low cost. [5,6] However, its calcium yield is unstable, which restricts the high-quality development of steelmaking.…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation of MnS inclusions mostly occurred in steel during cooling and during heating processes. [ 31,32 ] It was reported that MnS inclusions near the grain boundary of the steel were usually large and long and well deformed during steel rolling while MnS that precipitated around oxide inclusions were nearly spherical and difficultly deformed during steel rolling. [ 33–35 ] Inclusions in the heavy rail steel in the current study were mainly SiO 2 –Al 2 O 3 –MnO ones as SiMn deoxidation was performed.…”
Section: Introductionmentioning
confidence: 99%